Days with frog and toad eaudiobook - Lobel, Arnold (I Can Read, Level 2: Frog and Toad., 2008)
Frog and Toad enjoy spending their days together. They fly kites, celebrate Toad's birthday, and share the shivers when Frog tells a scary story. Most of all, they have fun together—every day of the year. Days with Frog and Toad is a Level Two I Can Read book, geared for kids who read on their own but still need a little help. Whether shared at home or in a classroom, the engaging stories, longer sentences, and language play of Level Two books are proven to help kids take their next steps toward reading success. The classic Frog and Toad stories by Arnold Lobel have won numerous awards and honors, including a Newbery Honor (Frog and Toad Together), a Caldecott Honor (Frog and Toad Are Friends), ALA Notable Children's Book, Fanfare Honor List (The Horn Book), School Library Journal Best Children's Book, and Library of Congress Children's Book.